Imitating Abraham ritual and exemplarity in Jewish and Christian contexts - Bergmann, Claudia D.; Blanton, Thomas R. 1968- (Leiden Boston Brill, 2025)
"Imitating Abraham provides exciting glimpses into the reception history of the character Abraham in Judaism, Christianity, and Islam, illuminating the manifold ways in which interpreters draw upon his legacy to authorize practices like sacrifice, circumcision, hospitality, feasting, prayer, and personal and corporate piety. Abraham holds surprises: his name is used in magical amulets-some published here for the first time-to ward off demons, protect cattle from illness, and even to round up runaway slaves. Researchers, students, and all interested in Biblical, Jewish, Christian, and Islamic Studies, as well as ritual and exemplarity will want to read this book"--
Includes index
Literaturangaben
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Abraham -- (Biblical patriarch); Abraham -- (Biblical patriarch) -- In rabbinical literature; Abraham -- (Biblical patriarch) -- In the New Testament; Abraham -- (Biblical patriarch) -- In the Qurʼan; Aufsatzsammlung